Assessing the Impact of Uncontrolled Space Object Re-entries on Air Traffic Management Operations - Chalabi, W.A.A.; Haagsma, A.; Badea, C.A.; Kok, J.T.A. (IAA, 2026)
With the growing number of activities in space, higher airspace, and conventional Air Traffic Management (ATM) domains, the likelihood of uncontrolled space object re-entries impacting airspace operations is increasing. Such events pose a potential safety threat to airborne traffic and challenge the efficiency of current ATM procedures. With the uncertainty of the exact time and location of a space object re-entry, and the velocities involved in orbit, it is proven difficult to have a specific and exact warning for an expected re-entry event. Recent real-world cases have shown inconsistent responses, ranging from complete airspace closures, causing significant disruptions and delays, to inaction, which may become untenable as space activity expands. This research addresses the question: How should ATM deal with uncontrolled re-entries from space? The study develops a use-case scenario in which a returning space object is detected shortly before its expected entry into Dutch airspace above Amsterdam Schiphol Airport, one of Europe's busiest hubs. A traffic simulation was developed to explore possible operational responses within this limited timeframe. Based on the simulation, a set of procedures is proposed to enable ATM to safely and efficiently manage such events. For instance, flights are categorized into critical and non-critical groups to facilitate prioritization, ensuring that aircraft most at risk or constrained by operational needs received immediate attention. In addition, the study identified the importance of providing controllers with visualization tools depicting the predicted impact zone and uncertainty area and time window, allowing for better situational awareness and decision-making under time pressure. The study concludes that a structured approach combining improved space object tracking capabilities, predefined risk assessment zones, and collaborative decision-making between ATM and space operations stakeholders can significantly enhance both safety and efficiency during uncontrolled re-entry events. Recommendations are proposed for integrating these procedures into existing ATM frameworks to better prepare for the increasing interaction between the space and aviation domains.